If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1z = 45 Solving 15 + -1z = 45 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1z = 45 + -15 Combine like terms: 15 + -15 = 0 0 + -1z = 45 + -15 -1z = 45 + -15 Combine like terms: 45 + -15 = 30 -1z = 30 Divide each side by '-1'. z = -30 Simplifying z = -30
| 9x+17=8x-41 | | -4y+8=-8y-12 | | 6x-6=14x-14 | | -14-r-6r=r+8 | | 2210=r(34) | | 42=2+6 | | 9-4b=6-5b | | 6-4(5+3y)=0 | | 8-1/2(-m-1) | | M+6=2m+11 | | 7v-15+7v=7v+48 | | 23=32x-425 | | 1680=336t | | 5(9x+6)=45x-4 | | 0.5x=-70 | | 3lx-1l=15 | | (3x+25)+(x-5)+x=180 | | -5-8=-13x-4 | | 2x+105=-3x+130 | | 7n+3=8+8n | | f(a+1)=(a+1)+8 | | a-43+a-43+w+43=a | | 9x+8=9x-2 | | 15*3-25+10= | | u+u+3=u+46 | | 3x-5(x-4)=-5+4x+13 | | 3x+9x-7=3(4x+4) | | 8t+40+16t-49=18t+23 | | 18x-12=3x^2 | | 7+6*2-2+8= | | 7a+21b=110 | | 2(1/6)*(3/26) |